Combining robotics with enhanced serotonin-driven cortical plasticity improves post-stroke motor recovery. (August 2021) - Conti, S.; Spalletti, C.; Pasquini, M.; Giordano, N.; Barsotti, N.; Mainardi, M.; Lai, S.; Giorgi, A.; Pasqualetti, M.; Micera, S.; Caleo, M.
Highlights: Robotic rehabilitation should be combined with neuromodulatory intervention. Serotonin may support stroke recovery by inducing cortical disinhibition. Combined treatment promoted recovery in general motor tests and manual dexterity. Abstract: Despite recent progresses in robotic rehabilitation technologies, their efficacy for post-stroke motor recovery is still limited. Such limitations might stem from the insufficient enhancement of plasticity mechanisms, crucial for functional recovery. Here, we designed a clinically relevant strategy that combines robotic rehabilitation with chemogenetic stimulation of serotonin release to boost plasticity. These two approaches acted synergistically to enhance post-stroke motor performance. Indeed, mice treated with our combined therapy showed substantial functional gains that persisted beyond the treatment period and generalized to non-trained tasks. Motor recovery was associated with a reduction in electrophysiological and neuroanatomical markers of GABAergic neurotransmission, suggesting disinhibition in perilesional areas. To unveil the translational potentialities of our approach, we specifically targeted the serotonin 1A receptor by delivering Buspirone, a clinically approved drug, in stroke mice undergoing robotic rehabilitation. Administration of Buspirone restored motor impairments similarly to what observed with chemogenetic stimulation, showing the immediate translational potential of this combined approach to significantly improve motor recovery after stroke.